EFFECTIVENESS OF USING DIGITAL TECHNOLOGIES AND FITNESS APPLICATIONS IN INCREASING PHYSICAL ACTIVITY AMONG UNIVERSITY STUDENTS (World Bulletin of Education and Learning, 2025)
Digital technologies and fitness applications have become increasingly influential tools in promoting physical activity among university students, particularly in the context of modern educational environments where sedentary lifestyles are common. This article examines the effectiveness of using digital platforms, mobile fitness apps, wearable devices, and virtual training programs to support students’ engagement in regular physical activity. The study highlights how technology-driven motivation, personalized exercise plans, real-time feedback, and progress monitoring can enhance physical fitness outcomes and encourage behavioral changes toward active living. Integrating digital resources into sport education contributes to students’ self-regulation, goal-setting skills, and understanding of healthy lifestyle habits. The research findings indicate that the use of fitness applications increases student interest in sports, improves adherence to exercise routines, and creates a more inclusive environment where physical activity becomes accessible beyond traditional training settings. Recommendations are offered for physical education departments to incorporate digital tools as part of their curriculum to improve student well-being, support instructors in monitoring development, and strengthen the connection between technological advancement and health education in higher institutions.
Keywords: Digital technologies, fitness applications, physical activity, university students, sport education, health promotion, wearable devices.